2019
DOI: 10.1177/1550147719842152
|View full text |Cite
|
Sign up to set email alerts
|

Security-enhanced three-factor remote user authentication scheme based on Chebyshev chaotic maps

Abstract: With the wide deployment of new computing paradigms, such as cloud computing and edge computing, the people can access services provided by remote servers more conveniently via the Internet. To preserve the security of those messages transmitted over the public channel, remote user authentication protocols are popularly implemented in various information systems. Recently, Park et al. pointed that Cao and Ge's three-factor authentication scheme suffers from offline identity guessing attack and server impersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…According to the results of previous analysis [28,38], we assume that the lengths of the identity, random number, and timestamp are 128, 64, and 32 bits, respectively, for a comparison of the communication costs. The hash function produces 160 bits; the block size of the symmetric encryption is 128 bits; the size of the Chebyshev polynomial is 128 bits; the size of the point multiplication on the elliptic curve is 160 bits.…”
Section: Performance Analysismentioning
confidence: 99%
“…According to the results of previous analysis [28,38], we assume that the lengths of the identity, random number, and timestamp are 128, 64, and 32 bits, respectively, for a comparison of the communication costs. The hash function produces 160 bits; the block size of the symmetric encryption is 128 bits; the size of the Chebyshev polynomial is 128 bits; the size of the point multiplication on the elliptic curve is 160 bits.…”
Section: Performance Analysismentioning
confidence: 99%
“…Zhao et al [43] have suggested a three-factor authentication mechanism based on Chebyshev chaotic maps for remote users and proved that their scheme can resist against all well-defined attacks, including impersonation attacks and offline password guessing attacks. However, Dharminder and Gupta [44] have demonstrated that chaotic maps-based security schemes fail to protect from stolen smart card attacks, identity guessing attacks, password guessing attacks, impersonation attacks, and session key attacks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xu and Wu 46 found that Xie et al's scheme 45 is vulnerable to desynchronization attacks, and proposed an improvement. 35 (A2, A3) 37,38 Choi et al 37 -Park et al 38 (A3, A4) 39 Zhao et al 39 -…”
Section: Single-server Environmentmentioning
confidence: 99%
“…In the same year, Park et al 38 also pointed out that Cao‐Ge scheme 35 is vulnerable to server impersonation and offline identity guessing attacks; they also proposed an improvement. Zhao et al 39 pointed out that Park et al's scheme 38 may suffer offline password guessing attacks, and does not achieve user untraceability and perfect forward secrecy; they proposed a security‐enhanced scheme using the extended Chebyshev chaotic maps. Reddy et al 40 modified two two‐factor–based anonymous MAKA schemes 41,42 to three‐factor–based anonymous MAKA schemes.…”
Section: A Brief Surveymentioning
confidence: 99%